2015
DOI: 10.3945/an.115.008433
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Advanced Glycation End Products and Their Role in Health and Disease

Abstract: Over the past 2 decades there has been increasing evidence supporting an important contribution from food-derived advanced glycation end products (AGEs) to the body pool of AGEs and therefore increased oxidative stress and inflammation, processes that play a major role in the causation of chronic diseases. A 3-d symposium (1st Latin American Symposium of AGEs) to discuss this subject took place in Guanajuato, Mexico, on 1-3 October 2014 with the participation of researchers from several countries. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
236
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 296 publications
(267 citation statements)
references
References 93 publications
(117 reference statements)
5
236
0
14
Order By: Relevance
“…Furthermore, AGE accumulation in collagen leads to changes in the biochemical and structural property of the components of the basement membrane affecting for example its elasticity, ionic charge, and thickness [50]. Accordingly, has been postulated that accumulation of AGE-crosslinking formed with vessel-wall collagen and basement membrane proteins, can contribute to vascular dysfunction [4,5]. In addition, AGE deposits have been found in atherosclerotic plaques and myocardium of patients with diabetes [2,52].…”
Section: Citation: Abate G Delbarba a Marziano M Memo M Uberti Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, AGE accumulation in collagen leads to changes in the biochemical and structural property of the components of the basement membrane affecting for example its elasticity, ionic charge, and thickness [50]. Accordingly, has been postulated that accumulation of AGE-crosslinking formed with vessel-wall collagen and basement membrane proteins, can contribute to vascular dysfunction [4,5]. In addition, AGE deposits have been found in atherosclerotic plaques and myocardium of patients with diabetes [2,52].…”
Section: Citation: Abate G Delbarba a Marziano M Memo M Uberti Dmentioning
confidence: 99%
“…Recently, different studies on mice and human have demonstrated that dAGEs can be absorbed at intestinal level, and be potentially toxic [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggest these three associations may be mediated through in situ enteral formation of fructose AGEs, which, after being absorbed, may contribute to inflammatory diseases via engagement of RAGE [15,[21][22][23]. Other food AGEs (preformed in cooking) have been shown to actually be absorbed and be pro-inflammatory in animal and human intervention studies [16]. They may participate in chronic inflammation enhancing insulin resistance in metabolic syndrome and diabetes as well as in renal failure [24][25][26] Given the ubiquity of ovalbumin and excess fructose in our diets, we reasoned that the possibility of an interaction between them during digestion needed exploration, especially in the light of the plausibility of this new hypothesis and our recent proof of principle study [27].…”
Section: Introductionmentioning
confidence: 99%
“…RAGE is involved in many inflammatory conditions [16][17][18][19]. RAGE is a pattern recognition receptor that binds AGE, among several ligands related to primary immunity [18][19].…”
Section: Introductionmentioning
confidence: 99%